ANALISIS STRATEGI PEMASARAN PEMBIAYAAN OTOMOTIF BERBASIS SYARIAH DI TOYOTA ASTRA FINANCE JAMBI - Siti Nurani, Anggun; Saputra Siregar, Erwin; Erliyana, Nova (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the marketing strategy of Islamic automotive financing at Toyota Astra Finance (TAF) Jambi Branch, identify the challenges encountered, and examine the company's efforts to improve marketing effectiveness. This research employed a qualitative descriptive approach. Data were collected through observations, interviews, and documentation involving the branch manager, Chief Marketing Officer, and employees, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the marketing strategy is implemented through murabahah-based financing products, direct marketing by marketing personnel, and customer education regarding Islamic financing principles. The strategy emphasizes honesty, trustworthiness, transparency, and fairness in its implementation. The main challenges include low public literacy on Islamic financing, the dominance of conventional financing, and limited promotional media. To address these challenges, the company has strengthened educational and promotional activities, improved employee competencies, and expanded public access to information on Islamic financing products. The study concludes that marketing strategies emphasizing education and Islamic values have the potential to enhance the competitiveness of Islamic financing and increase public interest in Sharia-compliant automotive financing.